Interferon-Independent Upregulation of Interferon-Stimulated Genes during Human Cytomegalovirus Infection is Dependent on IRF3 Expression - Ashley, Caroline L. (Viruses, 2019)
The antiviral activity of type I interferons (IFNs) is primarily mediated by interferon-stimulated genes (ISGs). Induction of ISG transcription is achieved when type I IFNs bind to their cognate receptor and activate the Janus Kinase/Signal Transducer and Activator of Transcription (JAK/STAT) signaling pathways. Recently it has become clear that a number of viruses are capable of directly upregulating a subset of ISGs in the absence of type I IFN production. Using cells engineered to block either the response to, or production of type I IFN, the regulation of IFN-independent ISGs was examined in the context of human cytomegalovirus (HCMV) infection. Several ISGs, including IFIT1, IFIT2, IFIT3, Mx1, Mx2, CXCL10 and ISG15 were found to be upregulated transcriptionally following HCMV infection independently of type I IFN-initiated JAK-STAT signaling, but dependent on intact IRF3 signaling. ISG15 protein regulation mirrored that of its transcript with IFNβ neutralization failing to completely inhibit ISG15 expression post HCMV infection. In addition, no detectable ISG15 protein expression was observed following HCMV infection in IRF3 knockdown CRISPR/Cas-9 clones indicating that IFN-independent control of ISG expression during HCMV infection of human fibroblasts is absolutely dependent on IRF3 expression.